Alternate Land Use Plan for a Peri-urban Watershed in Sub-tropical Humid Region of Meghalaya, India - Adelbert Kharlyndoh, Pratibha Thakuria Das, B.U. Chodhury and Vishram Ram, Carolyn Zothansiami, Pradip Kumar Bora (Journal of the Indian Society of Soil Science, 2018)
Land use planning based on land capability classification (LCC) was done for Nongpoh watershed located in perhumid hyperthermic subtropical climate in Meghalaya. Satellite data of IRS-P6 LISS-IV of December 2011 (spatial resolution of 5.8 m) was used as base map for the study. Standard visual interpretation based on tone, texture, pattern, shape and size was used for preparation of land use/land cover map. Soil profiles were exposed in each physiographic unit, studied for morphological properties and classified. Horizon wise soil samples were collected from representative pedons and analysed for their different physical and chemical properties. Arc-GIS software was used for digitization, data interpretation and thematic map preparation. Three crops viz., rice, maize and pineapple were assessed for their suitability for growing in the watershed area. Out of 265.91 ha watershed area only 10.97% area was suitable for paddy cultivation. Maize was suggested in few low-land areas where rice cultivation had some limitations. The upland hill soils with less than 15% slope are suggested for maize and pineapple cultivation besides agro-forestry. In the higher hill slope with slope of 15-45 per cent are suggested for pineapple or agro-forestry. Aforestation is suggested where land is not suitable for any kind of cultivation for better resource utilization in a sustainable way.